Asia meltdown the end of the miracle? - Gough, Leo (Capstone, 1998)
How Did Asia Get From Here… 1997 voted year of the Ringgit International Herald Tribune, 4 January 1997 To Here… Fair or foul, Yamaichi is no more Asahi Evening News, 23 January 1998 Malaysia accuses IMF of support for speculators The Daily Telegraph (London), 1 September 1997 Currency crisis taken to UN Stage Business Times (Malaysia) 27 September 1997. Bankruptcies break records, worst yet to come Asahi Evening News 20 January 1998 Japan debt shock raises pressure on Hashimoto South China Morning Past 13 January 1998 Is The Miracle Over?